Avaliação do conteúdo dos instrumentos de qualidade de vida aplicados em crianças e adolescentes com paralisia cerebral de acordo Classificação Internacional de Funcionalidade, Incapacidade e Saúde (CIF) - Teymeny, Andressa Andrade (2011)
Cerebral palsy (CP) is a group of motor disorders resulting from a lesion in the developing brain that can cause functional limitations and impair quality of live (QoL). The comparison of results from different studies and the choice of appropriate quality of life questionnaires is limited by the diversity of concepts and dimensions covered by these questionnaires. The International Classification of Functionality (ICF) has been used as a comparative interface in the analysis of QoL questionnaires. This study aimed at verifying and comparing the content of QoL questionnaires used to evaluate children and adolescents with CP according to the ICF. We identified 5 generic instruments and 5 specific ones used to evaluate the QoL of children and adolescents with CP in electronic databases. Two researchers independently analysed all the items and concepts of the questionnaires. Each item was linked to ICF categories by means of internationally recognized rules. The Kappa statistic was used to describe the degree of agreement among researchers. From the 488 items analyzed, 623 concepts were identified and 563 linked with 175 different categories of the ICF: 130 with the body function component, 333 with the activity/participation component, 50 with the environmental factors component and 50 with the personal factor component. Generic instruments, as well as specific ones had a higher number of concepts associated to the component activity/participation. The CP QOL Child was the instrument with the most balanced representation of the body function (20.0% of the concepts), activity/participation (36.2% of the concepts) and environmental factors (26.1% of the concepts) components. It also covered some concepts related to the personal factor component (9.2%) and others not included in the ICF (7.7%). The Kappa coefficients range between 0,80 at the 0,97. The study showed that QoL instruments applied to children and adolescents with CP mainly cover the activity/participation component and the body functions component of the ICF. The environmental factors and personal factors are not much studied. The body structures component was represented in only one item of the questionnaires. This analysis can guide clinicians and researchers in choosing the most appropriate instruments for the content to be evaluated.